Assessment of neurological symptoms and associated factors in patients with Wilson’s disease in Southwest China - Lu Zhang; Jieru Peng; Yao Dong; Qiwen Zhang; Wencheng Long; Yueshan Wang; Zhong Li; Lu Long; Yaxin Li; Qiaoling Jin; Lin Deng; Lin Cai; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Wilson’s disease is an inherited genetic disorder of hepatic copper metabolism characterized by hepatic, neurological, and psychiatric manifestations. Patients with neurological symptoms manifest remarkable variability regarding type and severity. This study aimed to characterize neurological signs and symptoms of patients with Wilson’s disease in Southwest China and identify factors associated with neurological symptoms in patients with Wilson’s disease. Methods A total of 109 treated patients with Wilson’s disease were included in the study. Sociodemographic and clinical data were obtained through face-to-face interviews and medical record reviews. ATP7B mutations were identified through whole-genome resequencing. Neurological signs and symptoms were assessed using the neurological part of the Unified Wilson’s Disease Rating Scale (UWDRS Part I). Multiple linear regression analysis was performed to assess the association between patient characteristics and UWDRS Part I scores. Results The most prevalent neurological symptoms of patients with Wilson’s disease were impaired rapid alternating movements of hands (76.2–81.0%), impaired finger tapping (75.0%), dysarthria (70.2%), salivation (66.7%), impaired handwriting (61.9%), impaired legs agility (60.7–61.9%), impaired gait (leg dystonia, 59.5%; ataxia, 58.3%), and dystonia of arms and hands (54.8–56.0%). Sex and age differences were observed in the neurological features of Wilson’s disease. Sociodemographic and clinical factors associated with the severity of neurological symptoms included occupation, family per capita monthly income, initial clinical subtype, adherence to low-copper diets, and mental health conditions, with an explanatory power of 42.1% (F = 10.474, p < 0.001). Genotype–phenotype analysis showed that patients carrying the p.P992L mutation had a significantly higher frequency of impaired finger tapping (p = 0.037). Conclusion The main neurological symptoms in this study of treated patients with Wilson’s disease were lack of motor coordination, dystonia, dysarthria, and salivation. This study identified five factors associated with the severity of neurological symptoms and revealed a potential association between the p.P992L mutation and a specific neurological manifestation. These results may enhance the understanding of Wilson’s disease, guide future management of patients to alleviate neurological symptoms and improve prognosis.